1998
DOI: 10.1007/bf02475257
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic properties of a mixed calcium-cobalt orthophosphate, II. Determination of the active sites in propan-2-OL dehydrogenation

Abstract: The effect of acidic (phenol) and basic (pyridme) poisons as well as that of water on propan-2-ol dehydrogenation were used to determine the nature of the active sites in the most active catalyst found in the mixed calcium-cobalt orthophosphate system, Ca3-xCox(PO4)2, with x = 0.32. A mechanism for catalyst action is discussed in light of the results obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Whitlockite or β-Ca 3 (PO 4 ) 2 -like compounds, for example, Ca 9 R(VO 4 ) 7 (R = rare-earth metals and Bi), have been extensively studied in expectation of their applications as nonlinear optical (NLO) materials. In Ca 9 Bi(VO 4 ) 7 , its NLO signal is about 3 times as large as that of KH 2 PO 4 . Tricalcium bis(phosphate), Ca 3 (PO 4 ) 2 , pure and doped with foreign cations has also been investigated as likely candidates for biomaterials, luminescent materials, and catalysts …”
Section: Introductionmentioning
confidence: 99%
“…Whitlockite or β-Ca 3 (PO 4 ) 2 -like compounds, for example, Ca 9 R(VO 4 ) 7 (R = rare-earth metals and Bi), have been extensively studied in expectation of their applications as nonlinear optical (NLO) materials. In Ca 9 Bi(VO 4 ) 7 , its NLO signal is about 3 times as large as that of KH 2 PO 4 . Tricalcium bis(phosphate), Ca 3 (PO 4 ) 2 , pure and doped with foreign cations has also been investigated as likely candidates for biomaterials, luminescent materials, and catalysts …”
Section: Introductionmentioning
confidence: 99%
“…β-TCP has been used as an ideal candidate for bone substitute, inorganic filling of biodegradable composites, substrate for evaluation of cell seeding efficacy, proliferation, osteogenic differentiation, and carrier for bone growth factors to stimulate bone healing and formation, because of its excellent osteoconductive and biodegenerative characteristics . Besides, it can also find other applications of this compound, which involve drug carrier, luminescence materials, and catalyst . It has been reported that the protein adsorption property of β-TCP is dependent upon its size and terminal facets .…”
Section: Introductionmentioning
confidence: 99%
“…Kobaltphosphat als heterogener Katalysator eingesetzt werden kann. [145,[146][147][148] In der chemischen Industrie ist Katalyse ein großes Thema, weil erst durch katalysierte Reaktionen eine schnelle, energiesparende und dadurch umweltschonende Produktion möglich wird.…”
Section: Schlussfolgerungunclassified
“…[180] Kobaltorthophosphat ist ein heterogener Katalysator, der die Reaktion der oxidativen Dehydrierung und Dehydratisierung von leichten Kohlenwasserstoffen katalysieren kann. Legrouri et al [146,147] untersuchten den Calcium-Kobaltphosphatkatalysator hinsichtlich aktiver Zentren an- Schema 3-1. Katalytische Reaktion von Butan-2-ol mit Sauerstoff zu den Produkten Buten und Butanon.…”
Section: üBerlegungen Zur Katalytischen Aktivität Von Kobaltphosphatunclassified